Hak Asasi Manusia dalam Konteks Penggusuran: Tinjauan Yuridis Terhadap Perlindungan PKL (Studi Penggusuran PKL di Puncak Bogor) - Ariono, Sujud; Windiyastuti, Feny (PT Elaborium Elevasi Indonesia, 2025)
This study examines the protection of Human Rights (HAM) related to the eviction of Street Vendors (PKL), with an example of the case of eviction of street vendors in the Puncak area, Bogor Regency. The existence of street vendors in the informal sector plays a vital role in the community's economy, but is often the target of eviction by the local government on the grounds of urban planning and public interest. In its implementation, the eviction is often carried out without a clear process, without appropriate relocation, and without considering the basic rights of the affected residents. The approach applied in this study is normative juridical, which involves legislative, conceptual, and case study methods. This study aims to analyze the practice of eviction from a legal and human rights perspective, and to assess its compliance with national regulations such as the 1945 Constitution and Law No. 39 of 1999, as well as with international instruments such as the International Covenant on Economic, Social and Cultural Rights (ICESCR). The research findings show that the eviction of street vendors in Puncak is not in accordance with human rights principles, because it is carried out without fair legal procedures and does not prioritize a participatory approach. Local governments, in this context, have yet to fully carry out their constitutional responsibilities to respect, protect and fulfill the rights of their citizens, especially vulnerable groups.